Bond strength of polymer clay with room temperature vulcanizing maxillofacial silicone - An in vitro study - Jayant N. Palaskar; Amit Dhansukhlal Hindocha; Tejas V. Nalawade; Shrishti R. Khurana; Anupama Patankar; Naisargi Shah (Wolters Kluwer Medknow Publications, 2024)
Aim: To assess and analyze the bond strength of polymeric organic clay and heat polymerized PMMA with RTV maxillofacial silicone with and without an adhesive primer. Settings and Design: The use of polymeric clay as a substructure for implant retained maxillofacial silicone prosthesis is suggested. However, the bond strength of polymeric clay with room temperature vulcanizing (RTV) maxillofacial silicone and heat polymerized polymethyl methacrylate(PMMA) with RTV maxillofacial silicone has yet to be studied. Materials and Methods: Fifty two samples were prepared in total. Group 1 (n = 13) silicone and PMMA without primer. Group 2 (n = 13) silicone and PMMA with primer. Group 3 (n = 13) silicone and polymer clay without primer. Group 4 (n = 13) silicone and polymer clay with primer. The samples were of dimensions of 75 mm × 10 mm × 3 mm. For groups 1 and 2, samples were fabricated with PMMA over which RTV silicone was manipulated, packed and vulcanized for 24 h. For Groups 3 and 4, polymer clay was molded to the required dimensions and hardened. RTV maxillofacial silicone was manipulated and packed over it and vulcanized. For Group 2 and 4 samples, primer was applied to the uncovered part of PMMA and polymeric clay respectively. The samples were subjected to a 180° and 90° (t peel test) peel strength test, respectively. Statistical Analysis Used: One way analysis of variance was used to analyze bond strength, which was then followed by a post hoc Tukey's test. Results: The mean bond strength of silicone and PMMA without primer was 0.35 ± 0.07 mN/m, while silicone and PMMA with primer had a mean bond strength of 0.41 ± 0.04 mN/m. The mean bond strength of silicone and polymer clay without primer and silicone and polymer clay with primer was found to be 0.45 ± 0.13 mN/m and 0.30 ± 0.05 mN/m, respectively. An 80% research power and a 95% confidence interval were used in the statistical analysis. A significance threshold of P < 0.05 was applied. Conclusion: The silicone to heat polymerized PMMA primer bond strength is the same as the silicone to polymer clay primer bond strength. Bond strength of polymer clay and maxillofacial silicone without primer is better than with primer. Therefore, without primer application, polymer clay substitutes PMMA as an interface between maxillofacial silicone material and attachments/keepers.